Departmental Committee on Labour And Social Welfare Report On The Employment Amendment Bill, 2019 No.15 Of 2019 - National Assembly (My University, 2019)
The Employment (Amendment) Bill (National Assembly Bill No. 15), underwent First Reading on 3rd April, 2019. Thereafter, the Bill was committed to the Committee on Labour and Social Welfare to review and report to the House pursuant to the provisions of Standing Order 216(5) (c). Consequently, the Committee, pursuant to Article 118 of the Constitution and Standing Order 127 (3), invited submissions from members of the public on the above Bill via advertisements in national dailies on 10th April, 2019. The Departmental Committee on Labour and Social Welfare received submissions on the Bill and upon lapse of the twenty-one days period prescribed under Standing Order 127(4) for presentation of the Committee's report, the Committee sought for extension of time which was granted by the Hon. Speaker. Thereafter, the Committee retreated to consider the submissions, deliberate on the provisions in the Bill and production of this report. May I take this opportunity to commend the Committee Members for their devotion and commitment to duty in the consideration of the Bill and express gratitude to the Offices of Speaker and Clerk of the National Assembly for providing technical and logistical support. On behalf of the Departmental Committee on Labour and Social Welfare and pursuant to the provisions of Standing Order 199 (6), it is my pleasant privilege and duty to present to the House a report of the Committee on the Employment (Amendment) Bill (National Assembly Bill No. 15).
Keywords: Employment amendment bill